Vitamin D deficiency at pediatric intensive care admission - Corsino Rey; David Sánchez-Arango; Jesús López-Herce; Pablo Martínez-Camblor; Irene García-Hernández; Belén Prieto; Zamir Pallavicini (Brazilian Society of Pediatrics, 2014)
Objective: to assess whether 25hydroxivitaminD or 25(OH)vitD deficiency has a high prevalence at pediatric intensive care unit (PICU) admission, and whether it is associated with increased prediction of mortality risk scores. Method: prospective observational study comparing 25(OH)vitD levels measured in 156 patients during the 12 hours after critical care admission with the 25(OH)vitD levels of 289 healthy children. 25(OH)vitD levels were also compared between PICU patients with pediatric risk of mortality III (PRISM III) or pediatric index of mortality 2 (PIM 2) > p75 [(group A; n = 33) vs. the others (group B; n = 123)]. Vitamin D deficiency was defined as < 20 ng/mL levels. Results: median (p25-p75) 25(OH)vitD level was 26.0 ng/mL (19.2-35.8) in PICU patients vs. 30.5 ng/mL (23.2-38.6) in healthy children (p = 0.007). The prevalence of 25(OH) vitD < 20 ng/mL was 29.5% (95% CI: 22.0-37.0) vs. 15.6% (95% CI: 12.2-20.0) (p = 0.01). Pediatric intensive care patients presented an odds ratio (OR) for hypovitaminosis D of 2.26 (CI 95%: 1.41-3.61). 25(OH)vitD levels were 25.4 ng/mL (CI 95%: 15.5-36.0) in group A vs. 26.6 ng/mL (CI 95%: 19.3-35.5) in group B (p = 0.800). Conclusions: hypovitaminosis D incidence was high in PICU patients. Hypovitaminosis D was not associated with higher prediction of risk mortality scores.